OMERE: A Long‐Term Observatory of Soil and Water Resources, in Interaction with Agricultural and Land Management in Mediterranean Hilly Catchments. Issue 1 (1st November 2018) - Molénat, J.; Raclot, D.; Zitouna, R.; Andrieux, P.; Coulouma, G.; Feurer, D.; Grunberger, O.; Lamachère, J.M.; Bailly, J.S.; Belotti, J.L.; Ben Azzez, K.; Ben Mechlia, N.; et al.
Abstract : Core Ideas: OMERE is a Mediterranean observatory of two farmed catchments in Tunisia and France. Water, contaminant, and erosion fluxes are monitored from plot to catchment scales. Soils and land use in relation with agriculture are surveyed. Scientific results concern elementary processes and integrated catchment functioning. Models were conceived for evaluation of land use and agricultural management scenarios. To account for the diversity of agricultural and ecosystem situations in hilly Mediterranean areas, the agro‐hydrological observatory OMERE (Observatoire Méditerranéen de l'Environnement Rural et de l'Eau) monitors two farmed catchments—one in northern Tunisia and the other in southern France. Mediterranean regions are typified by a highly variable climate, with an alternation of long droughts and intense storms, and by a strong heterogeneity of soil properties, due to a combination of climate, relief, parent materials, sparse vegetation, intense land use, man‐made infrastructure (ditches, terraces, etc.), and agricultural activities. In this context, OMERE aims to document the impacts of agricultural and land management on mass fluxes in Mediterranean farmed headwater catchments. The observation strategy is motivated by monitoring water, sediment, and contaminant fluxes and hydrologic and climatic variables at different spatial scales from cultivated plots and landscape elements to the catchment scale. These measurements have been performed at a fine time resolution over a long‐term scale and by surveying land use, agricultural practices, and soil surface characteristics. The long‐term observation strategy intends to support integrative multidisciplinary research for elucidating the conditions that improve soil and water management and delivery of ecosystem services in a Mediterranean rainfed cultivated context. The observatory has led to scientific insights regarding three scientific objectives: (i) to better understand the fluxes of water, erosion, and contaminants, especially pesticides, and of their natural and anthropogenic drivers on short‐ and long‐term scales; (ii) to analyze the aggregate effects of farming and land management on mass fluxes across scales, from plot to catchment or landscape scales; and (iii) to derive new scenarios for sustainable agricultural management and improved delivery of ecosystem services.